Люди 40-х годов: записки военного корреспондента - Жуков Юрий Александрович (1990)
Экземпляры: РБ (20221027) / Инвентарный номер: 20013 / Цена: 2.80 / Сис.шифр: 63.3(2)6 / Авт.знак: Ж 86 / ББК: 63.3(2)6